2013
DOI: 10.1103/physrevc.88.031302
|View full text |Cite
|
Sign up to set email alerts
|

Low-energy limit of the radiative dipole strength in nuclei

Abstract: We explain the low-energy anomaly reported in several experimental studies of the radiative dipole strength functions in medium-mass nuclei. These strength functions at very low gamma-energies correspond to the gamma-transitions between very close nuclear excited states in the quasicontinuum. In terms of the thermal mean-field, the low-energy enhancement of the strength functions in highly-excited compound nuclei is explained by nucleonic transitions from the thermally unblocked single-quasiparticle states to … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
73
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(78 citation statements)
references
References 38 publications
5
73
0
Order By: Relevance
“…[22,23]. The energy dependence of the BSFG model is in much better agreement with experimental data obtained from the 98 Mo( 3 He, 3 He'γ) reaction [24] than is the other often used model, the Constant-temperature (CT) model, see We considered two different values of the level density parameter a and the back shift energy E 1 from two different NLD parametrizations of von Egidy and Bucurescu [22,23]: a = 12.02 MeV −1 and E 1 = 0.68 MeV [22], and a = 11.28 MeV −1 and E 1 = 0.66 MeV [23]. The difference between these two parametrizations is due to (i) a different spin dependence of the NLD which is expressed via different values for the spin cut-off parameter and (ii) the introduction of a staggering in the number of levels with even and odd spins at low excitation energies in even-even nuclei.…”
Section: B Nuclear Level Density Modelssupporting
confidence: 77%
See 3 more Smart Citations
“…[22,23]. The energy dependence of the BSFG model is in much better agreement with experimental data obtained from the 98 Mo( 3 He, 3 He'γ) reaction [24] than is the other often used model, the Constant-temperature (CT) model, see We considered two different values of the level density parameter a and the back shift energy E 1 from two different NLD parametrizations of von Egidy and Bucurescu [22,23]: a = 12.02 MeV −1 and E 1 = 0.68 MeV [22], and a = 11.28 MeV −1 and E 1 = 0.66 MeV [23]. The difference between these two parametrizations is due to (i) a different spin dependence of the NLD which is expressed via different values for the spin cut-off parameter and (ii) the introduction of a staggering in the number of levels with even and odd spins at low excitation energies in even-even nuclei.…”
Section: B Nuclear Level Density Modelssupporting
confidence: 77%
“…The PSF consistent with such a low-energy enhancement was recently reported in 95 Mo also from analysis of 94 Mo(d,pγγ) data [2]. There exist theoretical explanations of a low-E γ enhancement utilizing both E1 [3] and M 1 [4,5] transitions. However, this enhancement is not supported by the data from two different 95 Mo(n,γ) experiments: (i) measure-ment of the two-step γ cascades (TSCs) following the capture of thermal neutrons using a HPGe detector coincidence setup [6], and (ii) measurement of spectra of the multi-step γ cascades (MSCs) following neutron capture at isolated resonances using the highly segmented BaF 2 Detector for Advanced Neutron Capture Experiments (DANCE) at Los Alamos [7].…”
Section: Introductionsupporting
confidence: 60%
See 2 more Smart Citations
“…On the other hand, in Ref. [3] the role of E1 transition has been studied in the finite-temperature relativistic quasiparticle random phase approximation and it has been found that a non-negligible a e-mail: kamila.sieja@iphc.cnrs.fr enhancement of the E1 strength is present in Mo nuclei in a given temperature range. So far, calculations of both M1 and E1 components of radiative strength function within the same framework have not been achieved and the exact mechanism responsible for the enhancement is not well understood.…”
Section: Introductionmentioning
confidence: 99%